2019
DOI: 10.2471/blt.18.224659
|View full text |Cite
|
Sign up to set email alerts
|

Training for hearing care providers

Abstract: The lack of an appropriately trained global hearing-care workforce is recognized as a barrier to developing and implementing services to treat ear and hearing disorders. In this article we examine some of the published literature on the current global workforce for ear and hearing care. We outline the status of both the primary-care workforce, including community health workers, and specialist services, including audiologists, ear, nose and throat specialists, speech and language therapists, and teachers of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…Some of the reasons identified in this review could influence the voluntary decision to participate in research. For example, (expected) personal or community health benefits, access to health care, (dis)trust or community pressure could affect autonomy in the consent to participate in research, or de facto constitute controlling influences affecting autonomy [15,112].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some of the reasons identified in this review could influence the voluntary decision to participate in research. For example, (expected) personal or community health benefits, access to health care, (dis)trust or community pressure could affect autonomy in the consent to participate in research, or de facto constitute controlling influences affecting autonomy [15,112].…”
Section: Discussionmentioning
confidence: 99%
“…Literature and international ethical guidelines for research conduct [14] mention a number of ways that could help to mitigate the potential threats of these reasons to participate to voluntary informed consent. Simultaneously, barriers to research identified in this review, such as need for/lack of social support, fear of stigmatisation, inconvenience and therapeutic misconception can also be addressed using these approaches [112,113].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations